Serum Level of High-Mobility Group Box Protein 1 as a Potential Treatment Target in Egyptian Sickle Cell Disease Patients - Arafat, Aya Mohamed Adel; Botros, Shahira K. A.; Afifi, Rasha; Zayed, Shahira Amin; Fateen, Mohamed (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: During tissue injury, high mobility group box 1 (HMGB1) is passively released from necrotic cells and actively secreted by inflammatory cells. Extracellular HMGB1 acts as an amplifier of Toll-Like Receptor (TLR)-dependent inflammation rather than a primary trigger of inflammation. We studied HMGB1 quantitative trait locus reference sequence 2249825 (rs2249825) and its serum level in both sickle cell disease (SCD) patients and healthy subjects to explore its possible role in the pathogenesis of vaso-occlusive crises (VOCs). Methods: HMGB1 rs2249825 was assayed in peripheral blood samples using real-time polymerase chain reaction (RT-PCR). While the serum level was assayed using a two-site enzyme-linked immunosorbent technique (ELISA). Results: Both the SCD patients and the control group had comparable HMGB1 rs2249825 genotype frequencies (P-value >0.05). SCD patients at their steady-state showed statistically significantly higher serum HMGB1 levels than the healthy controls, a median of 0.6 ng/ml with a range of 0.1- 85 ng/ml versus a median of 0.3 ng/ml and a range of 0.1-3 ng/ml (P-value <0.001), respectively. Statistically significant skewed high serum HMGB1 in the VOC samples in contrast to the steady-state samples was observed in the SCD patients with a median of 3.2 ng/ml and a range of 0.3-76.4 ng/ml versus a median of 0.2 ng/ml and a range 0.2-7.4 ng/ml (P-value <0.0001), respectively. Conclusion: HMGB1 could have a role in the VOC pathogenesis, hence it is suggested as a potential additive therapeutic target in SCD in general and in vaso-occlusions in specific. Keywords: Sickle cell disease, HMGB1, Hemoglobin S